Four Sources of Happiness in Buddhism - Shakya, Rajendra Prasad (Journal of International Buddhist Studies, 2019)
Every human being in the world is in search of happiness Today the goal of human being is acquiring happiness. Much attention is focused on Buddhism. Buddhism explain how to be happy and free from sufferings. Happiness and sorrow of our human life depends on way of life. Buddhism described middle way of life. In practicing middle way of Life a person can get a happy life. Central point of the happiness of Buddhism is based on the holy book Dhammapada. The Dhammapa describes: health, contentment, trust, peace (Nirbvana) or the aggregate which covers whole range of human Endeavour. Health Is Paramount, good health means free from disease of passions.Health is the highest gain of Contentment: an effective source of supreme happiness. Contentment is the greatest wealth. The best means of attaining supreme happiness is contentment.Trust: faith is also must for happiness. Faith is the base of social and spiritual system . Trust in parents is the best relation. The trusty whether related or not are the best kinsmen. The best kinsmen is a man you can trust. Peace is the highest bliss of perfect happiness. Nirvana is total cessation of all sufferings. It is the absolute negation of all pain Some Buddhist regard it’s as a state of pure bliss. Buddhism all these noble utterance should be put in to accrual practice in the course of ones daily life to happiness.